Evaluating Calcium Administration Protocols Around Farrowing on Sow Performance - Abigail K. Jenkins; Sierra M. Collier; Sara Virdis; Olivia J. Cataldo; Mike D. Tokach; Joel M. DeRouchey; Jason C. Woodworth; Katelyn N. Gaffield; Jordan T. Gebhardt; Robert D. Goodband; Kyle F. Coble; Paul J. Corns; et al. (Kansas Agricultural Experiment Station Research Reports, 2025)
A total of 933 mixed-parity sows (Line 1050, PIC) and their litters were used to evaluate the effect of calcium administration protocols around farrowing on sow performance. Sows were blocked by parity category and past stillbirth record, then allotted to one of three treatments with 310 to 312 replications per treatment. Treatments included: 1) control in which sows received no intervention; 2) 25 g of a calcium chloride-based product (CaCl; TRIAD, Alltech, Inc., Nicholasville, KY) top-dressed daily at the morning feeding from the time of entry (approximately d 112 of gestation) until the sow farrowed; or 3) calcium gluconate injection (CaG; VetOne; Boise, ID) where multiparous and primiparous sows received a 20 or 15 mL injection, respectively, if a sow had more than 16 piglets, longer than 1 h since the birth of the last piglet, the litter had two or more stillbirths, or farrowing duration exceeded 4 h. On a subset of females (n = 74/treatment), farrowing duration, sow blood metabolite analysis, sow urine pH, and piglet blood immunocrit were analyzed. Sow blood and urine were collected within 4 and 6 h of the end of farrowing, and piglet blood was collected within 24 h of the beginning of farrowing. Females were categorized in parity groups of P1 (n = 194), P2-P4 (n = 489), or P5+ (n = 250). Parity category, treatment, and their interaction were included as fixed effects, while the previous stillbirth category (< 0.5, ≥ 0.5 and ≤ 1, or > 1 average stillborn pigs per litter) was a random effect in the model. There were no differences in total born, percentage born alive, or percentage stillbirths between treatments; however, when at-risk sows (sows with > 16 piglets, > 1 hour since the last birth, ≥ 2 stillbirths, or farrowing lasting > 4 hours) were compared, administration of a CaG injection decreased stillbirths, increasing the percentage of pigs born alive. There was an interaction between farrowing calcium protocol and parity category for birth to cross-foster mortality (P = 0.035), where mortality was lowest in P1 control sows (P < 0.05) compared to all other combinations of treatment × parity category except for P1 CaG sows, which were intermediate. Sows fed CaCl had increased blood Cl and ionized Ca (P < 0.05) compared to control or CaG sows. Sows injected with CaG had increased blood glucose levels (P < 0.05) compared to control sows, with sows fed CaCl intermediate. Sows provided CaCl or CaG had decreased urine pH (P < 0.05) compared to control sows. There was a tendency for a farrowing Ca protocol effect on piglet immunocrit (P = 0.068), where offspring from CaG sows had a numeric increase in immunocrit ratios. In conclusion, in the overall population, top-dressing CaCl before farrowing or injecting CaG peripartum altered sow metabolites during farrowing but did not influence farrowing performance. However, when comparing at-risk sows among the three treatments, administration of a CaG injection decreased stillbirths, leading to an increase in the percentage of pigs born alive.
Keywords: calcium chloride; calcium gluconate; farrowing; sow; stillbirths